Representation of Sentani Women in the Jayapura Regency Legislative Institution for the 2019-2024 Period - Ibrahim Kristofol Kendi; Nona Riri I. P D; Setia Murni Parhusip (PT FORMOSA CENDEKIA GLOBAL, 2024)
The lack of Sentani women as members of the DPRD in Jayapura Regency does not illustrate that Papua is one of the provinces that is given space to express democratic life through the special autonomy policy which is predicted to be a new era for Papua towards progress or equality in political life. This research aims to explore the ability and capacity of the MRP in fighting for Sentani women's political rights in accordance with its duties and authority. Second, how is political recruitment carried out by political parties specifically for Sentani indigenous women cadres who are prepared to become legislative members. Third: the influence of local forces which then took away the privileges of sentani women so that they did not have the opportunity to pursue a career in politics. This research applies qualitative descriptive methods. Data was collected through observation, interviews and documentation. This research shows that the MRP's authority cannot be configured into political decisions that influence political parties to prioritize Papuan women in general and Sentani women in particular in political party management. In preparing cadres, political parties refer to the basic bylaws where the recruitment of cadres is guided by figures who are able to increase the party's electability. The influence of local forces in the Sentani cultural structure contributes to the minimal involvement of Sentani women in political participation.